Papers - New York Meeting – February, 1929 - Heat Treatment and Mechanical Properties of Copper-zinc and Copper-tin Alloys Containing Nickel and Silicon (With Discussion) - W. C. Ellis; Earle E. Schumacher (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
Nonferrous alloys upon which desirable properties can be conferred by heat treatment are becoming of increasing industrial importance. The alloys of copper with a constituent which has a solubility varying with temperature are materials of this character. Some of the constituents which are effective in producing a change in the mechanical properties of these alloys upon heat treatment are, according to Corson,' nickel and silicon, iron and silicon, cobalt and silicon, and chromium and silicon. In addition to these elements, Gregg2 states that the combination of beryllium and silicon is effective in producing age-hardening characteristics in copper. The effect of these elements, however, as dispersion-hardening constituents in the copper alpha solid solutions does not seem to have been studied in any considerable detail. This paper deals with the heat treatment and properties of three alpha brasses containing 3 per cent. of nickel plus silicon in the proportion necessary to form the compound nickel silicide, Ni2Si. Some information of a preliminary nature in regard to the hardening by heat treatment of phosphor bronze containing the same percentages of nickel and silicon is included. The method of hardening the alloys, which is effective in increasing the tensile strength and proportional limit, is similar to that used in the case of duralumin type aluminum alloys. It consists of a quench from a temperature at which the hardening constituent is in solid solution, followed by an aging at a lower temperature to precipitate the dissolved constituent in a dispersed condition. This results in an increased resistance of the alloy to deformation with an attendant improvement in the tensile properties.